Evaluating equilibrium and non‐equilibrium transport of ammonium in a loam soil column. Issue 1 (11th December 2017) - Hou, Lizhu; Hu, Bill X.; Qi, Zhiming; Yang, Huan
Abstract: Release of nitrogen compounds into groundwater, particularly those compounds from excessive agricultural fertilization, is a major concern in an aquifer recharge. Among the nitrogen compounds, ammonium ( NH 4 + ) is a common one. In order to assess the risk of agricultural fertilizer contamination to an aquifer through infiltration, NH 4 + adsorption onto a loamy agricultural soil profile (0–0.60 m depth) was studied using a soil column experiment and modelling simulation. The soil used in the experiment was drawn from an agricultural field in Xinzhen, Fangshan district, Beijing, China, and reconstituted in laboratory soil columns. Column experiments were conducted using bromide (conservative tracer) and NH 4 + ‐bearing aqueous solutions. The ammonium concentrations in the soil water samples were measured, and their values were plotted as the NH 4 + breakthrough curves. The chemical's soil–water distribution coefficients ( K d ) were calculated using breakthrough curves. Then the retardation factor ( R ) in saturated soil was calculated. For the NH 4 + ‐bearing aqueous solutions, the strongest NH 4 + adsorption occurred at the soil depth of 0.30–0.45 m. The convection–dispersion equation model and chemical non‐equilibrium model in Hydrus‐1D were used to simulate NH 4 + transport in the loamy soil. The two‐site chemical non‐equilibrium model in Hydrus‐1D was best to simulate NH 4 + transport through the soil column. Parameter sensitivity study was conducted to investigate the influences of solute transport by K d, the fraction of exchange sites assuming to be in equilibrium with the solution phase ( f), the longitudinal dispersivity ( λ ), and the first‐order rate coefficients (ω). The sensitivity analysis results indicate K d is the most critical parameter.